Multiplikasi Tunas Meriklon Kentang Pada Berbagai Jenis dan Konsentrasi Sitokinin - Mia Munggarani; Erni Suminar; Anne Nuraini; Syariful Mubarok (Faculty of Agriculture, Pattimura University, 2018)
Mericlone shoots are shoots of propagation using meristem explants which aim to produce seeds in a short time, large number, and disease-free seed. The aim of this experiment was to find out the best types and concentration of cytokinin to mericlone shoot multiplication of potato Jala Ipam variety. The experiment was carried out at Seed Technology Tissue Culture Laboratory of Agriculture, Padjadjaran University during November 2016 until February 2017. The experimental design was Completely Randomized Design with 13 treatments and 4 replications. Murashige and Skoog Medium with different concentration and types of cytokinine was used in this experiment. The result showed that the type and concentrations of cytokinin give the different effect on the mericlone shoot multiplication of potato Jala Ipam variety. MS medium with the additional of cytokinin 2 -iP 1.5 mg L-1 significantly increased the mericlone shoot multiplication of potato Jala Ipam variety at the variable number of leaves, number of nodes, and the number of branches.